(untitled) (Faridpur Medical College Journal, 2025)
Renal diseases are increasingly common causes of childhood morbidity and mortality. To find the prevalence of kidney diseases among school children in rural area of Bangladesh, this cross-sectional study was conducted in National Institute of Kidney Diseases and Urology, Dhaka from January 2018 to December 2018. Total 2401 school children of downtown of Dhaka were included in this study. Urine from all children were collected and examined by dipstick and light microscopy. In this study, 2401 children were screened, of them 1123 (46.8%) were boys and 1278 (53.2%) were girls. Prevalence of urinary abnormalities detected by first dipstick test was (2.83%) and second test was (2.21%). Urinary tract infection was the most common abnormality (1.33%) and Proteinurea was the second most common abnormality found in this study (0.58%) (Isolated proteinurea was 0.33%). In this study, hematuria was detected in 0.54% children (isolated hematuria is 0.29%). Prevalence of combined hematuria and proteinuria was 0.25%. When it comes to identifying hidden kidney disorders in children who are asymptomatic, urine screening is essential. Thus, urinary screening aids in the early detection of renal disorders and offers a structural work-up for a subsequent strategy that could result in their prevention, diagnosis, and treatment. Faridpur Med. Coll. J. 2025;20(2):25-28